From Loverholic Robotronic to All the Girly Girls : A content analysis of English usage in Korean pop song lyrics - Ranta, Aune (My University, 2025)
The aim of the thesis is to look into the phenomenon of the use of English in Korean Pop – commonly shortened to K-Pop – song lyrics. The thesis focuses on whether the use of English has increased within the last 15 years and what the reasons behind this phenomenon are using content analysis and theory of code-switching. The core materials of the thesis consist of a group of forty K-Pop songs from the years 2007 through 2010 and 2021 through 2024 - 20 songs from each span of time. These songs’ lyrics were written down and analysed, paying special attention to the amount of English versus Korean words used within a song. Results acquired through the materials indicate an increase in the use of English when comparing songs from the late 2000s and early 2010s to songs released in the 2020s. Fully or mostly Korean song lyrics have become rare, with songs with mostly English lyrics making an appearance. Although reasons for the use of English are numerous, core findings include marketability to an international audience, global spread of the English language as well as the catchiness of song lyrics. This topic needs further research, and conclusive results are hard to make pertaining to the increase of English given the relatively small sample size.
Keywords: K-Pop, code-switching, content analysis